Versatile Production of Poly(Epsilon-Caprolactone) Fibers by Electrospinning Using Benign Solvents - Liverani,L; Boccaccini,AR (Nanomaterials, 2016)
The electrospinning technique is widely used for the fabrication of micro- and nanofibrous structures. Recent studies have focused on the use of less toxic and harmful solvents (benign solvents) for electrospinning, even if those solvents usually require an accurate and longer process of optimization. The aim of the present work is to demonstrate the versatility of the use of benign solvents, like acetic acid and formic acid, for the fabrication of microfibrous and nanofibrous electrospun poly(epsilon-caprolactone) mats. The solvent systems were also shown to be suitable for the fabrication of electrospun structures with macroporosity, as well as for the fabrication of composite electrospun mats, fabricated by the addition of bioactive glass (45S5 composition) particles in the polymeric solution.